Implementing the GF Resource Grammar for Nepali Language - Simkhada, Dinesh (My University, 2012)
The Resource Grammar Library is a very important part of Grammatical Framework. The resource grammar mainly contains morphological and syntactic modules and implements a common abstract syntax. This work focuses on writing a complete implementation of Nepali computational grammar in Grammatical Framework. It tries to cover in-depth details of morphological and syntactic structures of the Nepali language and the way we formalize these grammatical details in the abstract structure that the Grammatical Framework provides. The current implementation can be used for multilingual applications just like any other language that is present in Grammatical Framework. The grammar covers as much details as possible on both morphological and syntactic level, so claiming this implementation to be one of the most comprehensive computational grammar for Nepali language won't be wrong. The correctness of this work has been verified by feedback from native Nepali speakers about the correctness of the examples in the GF resource grammar API.
Keywords: Datavetenskap (datalogi); Computer Science